Ideal Leader Behaviour in the Workplace - Nyiayu Olivia Miranda Bakrie; Gilang Rafi Chandra; Gemerlang Adhityatama; Sekar Wulan Prasetyaningtyas (Universitas Prasetiya Mulya, 2022)
Entrepreneurs in Indonesia believe that digital products and services may enable a more efficient and effective way of living. The key to achieving success in the era of digital transformation is to disrupt the market by providing consumers with exceptional value. In order to execute this correctly, businesses must be both effective and effective in achieving this expectation. Today Indonesian large businesses are digitalized and prepared to create disruptive, consumer-focused innovation as a result of this effort. In addition, as of 2022, Indonesia had the highest number of digital start-up enterprises among Southeast Asian nations, with 2,345 registered. Leadership is a factor in the success of digital firms, and digital businesses that must develop for the benefit of other companies are no exception. We believe that significant effort needs to be done in order to grasp the leadership behavior of the executives in payment aggregator firms. This research was conducted at Tangerang Indonesia-based software and consulting business. Since 2014, the company's main focus has been billing aggregation, and it currently has over 150 partners. Interviews were conducted in Indonesian, which would subsequently be translated into English for the purpose of this research. The outcomes showed that corporate leaders of a billing aggregator company have three types of behaviors that are considered desirable for their staff. Relationship-related, performance-related, and conflict-related behaviors are all interconnected. Ideal leaders establish clear boundaries not only between jobs but also between their relationships with employees.